2008
DOI: 10.1007/s11274-008-9849-5
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of epiphytic yeasts with potential for biological control of green mold of citrus fruits

Abstract: Epiphytic yeasts isolated from the surface of citrus fruits, harvested in several orchards in the SoussMassa-Drâa Valley, Agadir, Morocco, were in vivo screened for antagonistic activity against Penicillium digitatum, the causal agent of green mold of citrus. From a total of 245 yeast strains assessed for their biocontrol activity against P. digitatum, fifteen reduced the incidence of disease to less than 50%. The effectiveness of the best selected yeast strains showed that Pichia anomala (YT73), Debaryomyces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 31 publications
0
35
0
1
Order By: Relevance
“…In the wounds, yeast growths rapidly, but on intact fruit surfaces the antagonist populations usually diminish to the level of natural epiphytic microflora (Droby et al, 2009;Liu et al, 2013). In these sense, the use of adjuvants like Tween 80 (as surfactant) or dextrose (as nutrient) could be an alternative to a better distribution and maintaining of antagonistic yeast population on carposphere at concentrations suitable for biological control, as previously reported (De Cal et al, 2012;Spadaro and Droby, 2016 (Chalutz and Wilson, 1990;Droby et al, 1999;Taqarort et al, 2008). In a recent study marine D. hansenii was capable to inhibit the mycelial growth of pathogenic fungi of maize (Zea mays L.) (Medina-Córdova et al, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…In the wounds, yeast growths rapidly, but on intact fruit surfaces the antagonist populations usually diminish to the level of natural epiphytic microflora (Droby et al, 2009;Liu et al, 2013). In these sense, the use of adjuvants like Tween 80 (as surfactant) or dextrose (as nutrient) could be an alternative to a better distribution and maintaining of antagonistic yeast population on carposphere at concentrations suitable for biological control, as previously reported (De Cal et al, 2012;Spadaro and Droby, 2016 (Chalutz and Wilson, 1990;Droby et al, 1999;Taqarort et al, 2008). In a recent study marine D. hansenii was capable to inhibit the mycelial growth of pathogenic fungi of maize (Zea mays L.) (Medina-Córdova et al, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…It has been reported that the impact of these pathogens on the citrus industry differ from country to country. In Morocco, the losses have been estimated at over 60% and are generally controlled by applying chemical fungicides before or after harvesting (Taqarort et al, 2008). Imazalil, thiabendazole (TBZ) and sodium o-phenylphenol (SOPP) are the most commonly used synthetic chemical compounds in Morocco (Lahlali et al, 2004(Lahlali et al, , 2005 and worldwide to control postharvest mould infections (Lahlali et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that, among 21 medicinal and aromatic plants tested, Thymus leptobotrys, Cistus villosus, and Peganum harmala plants completely suppressed the growth of P. italicum, P. digitatum and G. candidum in controlled conditions. Taqarort et al (2008) screened three effective epiphytic yeast strains, P. anomala (YT73), Debaryomyces hansenii (YT22) and Hanseniaspora guilliermondii (YT13) against P. digitatum among a collection of 245 strains. The objective of this work was to investigate the effectiveness of epiphytic yeast P. guilliermondii strain Z1, isolated from the surface of healthy orange fruit, as an eventual biocontrol agent (BCA) of citrus blue mould.…”
Section: Introductionmentioning
confidence: 99%
“…diseases that affect citrus fruit quality in Mediterranean climates (Lahlali et al, 2004;Palou et al, 2002). In Morocco, the losses have been estimated at over 60% and are generally controlled by applying chemical fungicides before or after harvesting (Lahlali et al, 2004(Lahlali et al, , 2005Taqarort et al, 2008). However, the usual appearance of strains resistant to chemicals, the increased concern for the environment and human health, and public demand for minimal residues have contributed to the development of alternative strategies to substitute the use of synthetic chemicals.…”
Section: Introductionmentioning
confidence: 99%